Contradiction Between the Average Age of Retirement at the Time of Death and the Average Pension Time for Men and Women in Public Employment in Portugal - Nunes, Pedro; Miranda, Eva (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2010)
The short article attempts to make some very brief reflections on the effects a lack of public policies positively discriminatory in terms of public employment retirement. In particular, the observation of the absurd contradiction between the average age of retirement at the time of death (for men and women) and the average pension time for men and women in public employment in Portugal.